Local business capacity to scale new hybrid maize seeds: Insights from a decade of tracking sales in Mexico - Donovan, Jason A.; Peña Castellon, Carmen Meliza; Rutsaert, Pieter (SAGE Publications, 2024)
The return on investments from public-sector hybrid maize breeding depends heavily on the capacities of locally owned, small- and medium-sized seed enterprises (maize SMEs) to build market share for new products. In Mexico, between 2011 and 2020, dozens of maize SMEs obtained new genetic material through a hybrid maize breeding program funded by the Mexican government and led by the International Maize and Wheat Improvement Center (CIMMYT). To examine the maize SMEs’ ability to expand sales of new seed products, we tracked sales for 16 maize SMEs between 2014 and 2022. Our analysis captured variation in capacity by grouping the SMEs by seed sales volumes: emerging group (EG), small-sized group (SG), and medium-sized group (MG). The results showed the capacity of the MGs to launch and scale new seed products and remove older products from the market. The EGs and SGs expanded sales of new products, but also maintained production of older products, including open-pollinated varieties. However, during the observation period we detected little growth in total sales volumes across the three groups. The findings suggest that future efforts to promote local maize SMEs will benefit from a balanced approach between technology transfer and seed system development. We recommend that future seed systems investments consider: (1) support for innovation in seed-product marketing, (2) coordinated public-sector purchases that prioritize new products, and (3) innovation in product design for niche market development. These lessons may also serve future efforts to design regional-level programs in support of smallholder rainfed hybrid maize production.